2020
DOI: 10.1039/d0ra05230b
|View full text |Cite
|
Sign up to set email alerts
|

2D black phosphorus and tungsten trioxide heterojunction for enhancing photocatalytic performance in visible light

Abstract: BPNs in the WO3–BPNs heterojunction acted as a co-catalyst to enhance photo-generated electron–hole pairs separation and improve degradation performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The C 1s peak observed is attributed to the charge correction before deconvolution was conducted. Based on Figure b, deconvolution of the P 2p spectrum of the RP/BP sample unveils two narrow peaks situated at 130.42 and 131.29 eV, which could be assigned to elemental P 2p 3/2 and 2p 1/2 of the P–P bonds, respectively, whereas a weaker and wider sub-band is apparent at approximately 135.02 eV, implying the presence of oxidized P species (P x O y ) . Comparatively, the two characteristic peaks of P 2p 3/2 and 2p 1/2 of the RP/BP@WO 3 sample situated at 129.70 and 130.60 eV, respectively, experience weakened intensities with the appearance of a new peak located at 133.90 eV, which could be ascribed to the formation of P–O–P, as validated by the O 1s spectra (Figure d).…”
Section: Resultsmentioning
confidence: 92%
“…The C 1s peak observed is attributed to the charge correction before deconvolution was conducted. Based on Figure b, deconvolution of the P 2p spectrum of the RP/BP sample unveils two narrow peaks situated at 130.42 and 131.29 eV, which could be assigned to elemental P 2p 3/2 and 2p 1/2 of the P–P bonds, respectively, whereas a weaker and wider sub-band is apparent at approximately 135.02 eV, implying the presence of oxidized P species (P x O y ) . Comparatively, the two characteristic peaks of P 2p 3/2 and 2p 1/2 of the RP/BP@WO 3 sample situated at 129.70 and 130.60 eV, respectively, experience weakened intensities with the appearance of a new peak located at 133.90 eV, which could be ascribed to the formation of P–O–P, as validated by the O 1s spectra (Figure d).…”
Section: Resultsmentioning
confidence: 92%
“…In contrast, a broader and wider sub‐band can be found at 135.02 eV, suggesting that oxidized P species (P x O y ) is present. [ 27 ] Contrastingly, the P 2p 3/2 and 2p 1/2 characteristic peaks of the BiVO 4 –Ov@RP/BP sample located at 129.78 and 130.65 eV experience diminished intensities with the formation of two new peaks situated at 133.18 and 134.25 eV, attributing to the generation of O–P=O and P–O, respectively. [ 28,29 ] Notably, the P 2p 3/2 and 2p 1/2 XPS peaks for BiVO 4 –Ov@RP/BP are shifted toward lower binding energies with a difference of 0.64 eV in comparison to the RP/BP sample.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wang et al certificated that BP can effectively enhance the PEC performance of the WO 3 /BP heterojunction because the band gap of BP (0.5 eV) is much lower than that of WO 3 (2.5 eV), and the lower band gap energy is more likely to stimulate the generation of photogenerated electron−hole pairs. 59 Besides, several research studies have focused on the Bi-based semiconductors due to their excellent electrical, optical, and non-toxicity properties, such as bismuth salt (BiVO 4 ) and bismuth oxysulfides (Bi 2 O 2 S, Bi 2 OS 2 , Bi 10 O 6 S 9 , etc.). 60−62 For instance, Zhang et al synthesized a BP/BiVO 4 (010) heterostructure, which can accelerate the transfer rate and prevent the recombination of photogenerated carriers due to the built-in electric field and narrow band gap structure of the formed type-II heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on obtaining better photogenerated charge separation and transfer by adding BP material. For example, Wang et al certificated that BP can effectively enhance the PEC performance of the WO 3 /BP heterojunction because the band gap of BP (0.5 eV) is much lower than that of WO 3 (2.5 eV), and the lower band gap energy is more likely to stimulate the generation of photogenerated electron–hole pairs . Besides, several research studies have focused on the Bi-based semiconductors due to their excellent electrical, optical, and non-toxicity properties, such as bismuth salt (BiVO 4 ) and bismuth oxysulfides (Bi 2 O 2 S, Bi 2 OS 2 , Bi 10 O 6 S 9 , etc.…”
Section: Introductionmentioning
confidence: 99%